Cross-protective efficacy of the O1 Manisa + O 3039 bivalent vaccine and the O 3039 monovalent vaccine against heterologous challenge with FMDV O/Jincheon/SKR/2014 in pig. Issue 12 (14th March 2019) - Kim, Taeseong; Hong, Jang-Kwan; Oem, Jae-Ku; Lee, Kwang-Nyeong; Lee, Hyang-Sim; Kim, Yong Joo; Ryoo, Soyoon; Ko, Young-Joon; Park, Jong-Hyeon; Choi, Jida; Lee, Seung Heon; Jo, Hye Jun; et al.
Abstract: After massive foot-and-mouth disease (FMD) outbreaks originated from Jincheon County from Dec. 2014 to Apr. 2015, the effectiveness of the previous FMD vaccine containing only the O1 Manisa as the O antigen, O1 Manisa + A Malaysia 97 + Asia 1 Sharmir trivalent vaccine, was questioned in South Korea, and a change in the O antigen in FMD vaccines was demanded to control the FMD caused by FMDV O/Jincheon/SKR/2014, the O Jincheon strain. Therefore, the efficacies of O1 Manisa + O 3039 bivalent vaccine and O 3039 monovalent vaccine were studied for cross-protection against heterologous challenge with the O Jincheon strain. In this study, the efficacy of the O1 Manisa + O 3039 bivalent vaccine was better than that of the O 3039 monovalent vaccine, even though the serological relationship (r1 value) between O Jincheon and O 3039 was matched according to the OIE Terrestrial Manual. According to serological test results from vaccinated specific pathogen free pigs, virus neutralization test titers against Jincheon were good estimates for predicting protection against challenge. A field trial of the O1 Manisa + O 3039 bivalent vaccine was performed to estimate the possibility of field application in conventional pig farms, especially due to concerns about the effect of maternally derived antibodies (MDA) in field application of the FMD vaccine. According to the result of the field trial, the O1 Manisa + O 3039 bivalent vaccine was considered to overcome MDA. The results of the efficacy and field trials indicated that the O1 Manisa + O3039 vaccine could be suitable to replace previous FMD vaccines to control the FMD field situation caused by O Jincheon FMDV.